Juridical Analysis of Legal Protection for Creditors on Mortgage Rights Canceled by Decision - Cassy Mercylia Tahir; Sriwati; Dinda Silviana Putri (Journal of Law, Politic and Humanities, 2025)
Mortgage is a guarantee in providing credit facilities and aims to protect the interests of creditors and debtors. The creditor can execute the object of Mortgage collateral if the debtor defaults. However, if the object of collateral experiences a dispute and the transfer of rights is canceled by a Court Decision, what are the legal consequences. The research method used is to use normative research that uses primary legal sources consisting of laws and regulations, legal principles, legal principles and legal doctrines on legal systematics related to answering problems in the subject of writing. From the results of the analysis and discussion that Bank BTN Persero is a good faith creditor in granting credit, and has been in accordance with standard operating procedures, and has not violated the laws and regulations, canceled Mortgage Rights by Court Decision does not cause the Debtor's debt to be canceled, the Creditor can take legal action for Wrongful Acts to request compensation for the actions that have been caused and request other assets / assets in exchange for Mortgage Rights that have been canceled previously by Court Decision.